The impact of sampling approach and daily water usage on lead levels measured at the tap. (1st June 2021) - Lytle, Darren A.; Formal, Casey; Cahalan, Kelly; Muhlen, Christy; Triantafyllidou, Simoni
Highlights: Lead in water from the LSL reached equilibrium after 7 to 15.5 h. Sequential profiles accurately identified the LSL location. Peak profile lead levels were a fraction of lead measured directly from the LSL. RDT and manual composite sample lead levels were ≥ first draw lead levels. Daily water usage impacted total lead levels; lower use increased lead. Graphical abstract: Image, graphical abstract Abstract: There are many sampling approaches available for lead (Pb) in drinking water. Selecting the best approach for its intended use is critical. The objective of this work was to compare water Pb levels collected by multiple sampling approaches from a model home plumbing system (HPS) that included an old Pb service line (LSL), as a function of daily water usage. Specifically, flushed, direct LSL, sequential profile, random daytime (RDT), first draw, and manual composite samples were compared, and daily water usage rates ranged from 1.4 to 120 gallons/day (5.3–454.2 L/day). Pb levels in water collected directly from the LSL reached equilibrium after 7–15.5 h of stagnation, and approximately 55% of the equilibrium Pb concentration was reached after 2 h. Sequential sampling accurately identified the LSL; however, the peak profile Pb concentrations were a fraction of the Pb measured directly from the LSL. Daily water usage patterns greatly impacted total Pb levels in all water sampling approaches, although manual composite and RDT samples were more sensitive to changes. Manual composite and RDT samples were equal to or greater than first draw samples throughout the study, and differences grew larger as water usage decreased.